Tunable spin-state bistability in a spin crossover molecular complex. (22nd May 2019) - Jiang, Xuanyuan; Hao, Guanhua; Wang, Xiao; Mosey, Aaron; Zhang, Xin; Yu, Le; Yost, Andrew J; Zhang, Xin; DiChiara, Anthony D; N'Diaye, Alpha T; Cheng, Xuemei; Zhang, Jian; et al.
Abstract: The spin crossover (SCO) transitions at both the surface and over the entire volume of the [FeH2 B(pz)2 2 (bipy)] polycrystalline films on Al2 O3 substrates have been studied, where pz = pyrazol-1-yl and bipy = 2, 2′-bipyridine. For [FeH2 B(pz)2 2 (bipy)] films of hundreds of nm thick, magnetometry and x-ray absorption spectroscopy measurements show thermal hysteresis in the SCO transition with temperature, although the transition in bulk [FeH2 B(pz)2 2 (bipy)] occurs in a non-hysteretic fashion at 157 K. While the size of the crystallites in those films are similar, the hysteresis becomes more prominent in thinner films, indicating a significant effect of the [FeH2 B(pz)2 2 (bipy)]/Al2 O3 interface. Bistability of spin states, which can be inferred from the thermal hysteresis, was directly observed using temperature-dependent x-ray diffraction; the crystallites behave as spin-state domains that coexist during the transition. The difference between the spin state of molecules at the surface of the [FeH2 B(pz)2 2 (bipy)] films and that of the molecules within the films, during the thermal cycle, indicates that both cooperative (intermolecular) effects and coordination are implicated in perturbations to the SCO transition.